Strategy of the Outer Baduy community of South Banten (Indonesia) to sustain their swidden farming traditions by temporary migration to non-Baduy areas - BUDIAWATI SUPANGKAT ISKANDAR; JOHAN ISKANDAR; RUHYAT PARTASASMITA (Society for Indonesian Biodiversity, 2018)
Iskandar BS, Iskandar J, Partasasmita R. 2018. Strategy of the Outer Baduy community of South Banten (Indonesia) to sustain their swidden farming traditions by temporary migration to non-Baduy areas. Biodiversitas 19: 453-464. The Baduy people live in the forest village of Kanekes, in Leuwidamar sub-district, Lebak district, Banten Province, Indonesia. They have long practiced a form of swidden farming based on traditional ecological knowledge and beliefs about the cosmos. Unlike the rest of the surrounding Sundanese society, the Baduy have prohibited wet rice field cultivation on their lands. Moreover, in conserving their traditional swidden farming system, the Baduy people have resisted the use of modern rice varieties, inorganic fertilizers, and synthetic pesticides. On the basis of Baduy culture, their swidden-produced rice is not sold, and for at least the past 50 years the harvested rice has not been stored away in barns but instead has been mainly used for daily home consumption and various traditional rituals. Nowadays, Baduy swidden farming is affected by many new pressures – particularly by population increase, and increasing food demand – but the forest land used for practicing their swidden farming is limited. Therefore, in order to maintain the sustainability of their swidden farming system, the Baduy people, particularly the Outer Baduy, have developed cultural strategies that include temporary outmigration (nganjor) to neighboring, non-Baduy areas where Muslim value-systems provide the main cultural dynamic. The aim of the study reported in this paper was to elucidate the cultural strategy of the Outer Baduy to maintain their sustainable swidden farming by temporary out-migration to non-Baduy areas in territory of the Muslim majority. The method used in this study was qualitative based on an ethno ecological approach. Several techniques were used, namely direct observation, participant observation, and deep interviews with competent informants who were purposively selected. The results of the study confirmed that up until now the Outer Baduy have maintained the sustainability of their swidden farming, by various means, especially by conducting contemporary outmigration to non-Baduy areas in Muslim majority territory. They plant swidden rice in a way that fulfills various traditional rituals, and by diversifying their non-rice-trading options that include growing a variety of mainly tree crops in their swidden land (huma) and in other anthropogenic land. This involves occasional negotiated out-migration to non-Baduy area for temporary swidden farming in surrounding Muslim majority territory. This has enabled the Outer Baduy swidden farming system to be maintained on a long-term basis.